George Gershwin - Jeambar, Denis 1948- (Paris Mazarine, 1998)
In 1904, a six-year-old Jewish boy of Russian origin was wandering the streets of New York. Suddenly, a player piano played Anton Rubinstein's Melody in F. It was love at first sight: this kid among many would become the most illustrious composer in the New World, at a key period when the United States, at the height of its power, was plunged into a terrible economic crisis. Born into poverty on 26 September 1898, George Gershwin died a wealthy man on 11 July 1937 after writing his masterpiece Porgy and Bess. The thirty-nine years of his life are reminiscent of a blockbuster script. In the foreground: dinner jackets, cocktails, flattering relationships and delirious audiences. In the background: racism, unemployment, nightclubs and brothels. Gershwin or the genius of contrast. (Translated with DeepL.com)
Keywords: Gershwin, George -- 1898-1937; 20th Century (1901-2000); Composer; Biography; USA